INPROVEMENT OF SCIENCE LEARNING OUTCOMES USING AUDIO-VISUAL MEDIA ON LEARNING THE PROPERTIES OF LIGHT - Rusmiati Aliyyah, Rusi; Malia, Yesi (DIDAKTIKA TAUHIDI: JURNAL PENDIDIKAN GURU SEKOLAH DASAR, 2016)
This research is a classroom action research conducted collaboratively to determine the increase in student learning outcomes in learning the properties of light using audio-visual media in class V SD Negeri Tajurhalang 01 District Cijeruk, Bogor regency, West Java province. Grand Tour beginning of the data shows the value of student learning outcomes as many as 29 people, only 7 students (24.13%), which reached KKM and 22 students (75.87%) who have not reached the KKM amounted to 60. The research model using Kemmis & McTaggart consisting of planning, acting, observing and reflecting the success criteria of the study 75% of students reached the KKM. Research shows that the average value of student learning outcomes VB class of 29 students in the first cycle to obtain a value of 48.62 completeness rate of 55.17%, and the second cycle obtain an average value of 63.44 with a level of mastery amounting to 75.87%. Similarly, the results of observations of students able to show activity in the learning cycle I obtained a value of 62.75% and the activity of students in the second cycle of 67.24%. As for the quality of teaching in the first cycle gained in value by 75.59% and the second cycle of 82.56%. So, that all aspects studied increased. On the quality of learning increases of 8.97%, 4.49% increase student activity and learning outcomes of students increased by 20.7%. This study suggests that the IPA Improved Learning Outcomes Using Audio Visual Media in Education Properties Elementary School fifth grade light Tajurhalang 01 District Cijeruk, Bogor regency of West Java Province can improve student learning outcomes and student activity in the learning process.